2018
DOI: 10.1063/1.5016596
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of different energy storage devices in AGC of multi-source system including geothermal power plant

Abstract: This paper highlights an attempt of comparing the performance of several energy storage (ES) devices such as battery ES, flywheel ES, capacitive ES, superconducting magnetic ES, ultra-capacitors, and redox flow batteries (RFBs) in automatic generation control of an interconnected system. The considered system comprises conventional thermal, hydro, wind, and solar photovoltaic generations wherein a geothermal power plant (GTPP) is also incorporated. The thermal and hydro systems are provided with appropriate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Thus, RFBs can play a key role in sustaining system frequency by regulating the real power mismatch between control areas, and are recommended in power systems to improve the quality of power generated through hybrid energy sources. The transfer function model of RFBs implemented in this work is from [27] and described in Eq. (11).…”
Section: Redox Flow Batteries (Rfbs)mentioning
confidence: 99%
“…Thus, RFBs can play a key role in sustaining system frequency by regulating the real power mismatch between control areas, and are recommended in power systems to improve the quality of power generated through hybrid energy sources. The transfer function model of RFBs implemented in this work is from [27] and described in Eq. (11).…”
Section: Redox Flow Batteries (Rfbs)mentioning
confidence: 99%
“…Hence to reduce the emissions of carbon, greenhouse gases, to generate more electricity at low cost, to mitigate energy crisis and to upgrade the conventional PS, renewable energy sources are necessary to incorporate in PS 5 . Tasnin and Saikia 6 studied the LFC problem incorporating wind, solar, geothermal power plant (GTPP), and energy storage elements with other conventional energy sources in an interconnected PS. It is expected that the installation of GTPP will increase rapidly worldwide, and analysts expect that by 2050, the production capacity will exceed 100 GW 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sahu et al 29 considered higher degree freedom integral order controller such as 2DOF‐PID as a secondary controller to obtain better dynamic performance. Cascaded controllers such as fractional order PI‐fractional order PID, 6 fuzzy PID‐filter‐(1+PI) 30 have been proposed as a secondary controller for LFC, to enrich PS performance. Lurie 31 introduced a new controller called Tilt‐integral‐derivative (TID) that consists of non‐integer power in proportional gain and shows more accurate tuning, improved disturbance elimination ability and reduced parameter uncertainties on the system performance, than other conventional controllers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent time, many authors have shown the superiority of fractional order controllers over classical controllers in the area of LFC mechanism. Novel of them are fractional order PID controller [5,19], PID μ F controller [7], cascade PI-FOPD controller [14], cascade tilted-integral-derivative controller [20], fractional-order PI-PID cascade controller [21] and cascade tiltintegral-tilt-derivative controller [22]. The controller gains are optimised by various meta-heuristic techniques like bacterial foraging optimisation [3,5], opposition-based harmonic search optimisation [6], lightning search algorithm [7], modified sine cosine algorithm [10], volleyball premier league algorithm [14], stochastic fractal search optimisation [15], hybrid bacteria foraging-particle swarm optimisation (PSO) [16], modified group search optimisation [17], antlion optimiser [18], PSO [19], salp swarm algorithm (SSA) [20], sine cosine algorithm [21] and water cycle algorithm [22].…”
Section: Introductionmentioning
confidence: 99%